2016
DOI: 10.1021/acs.nanolett.6b00771
|View full text |Cite
|
Sign up to set email alerts
|

Nanofiber Air Filters with High-Temperature Stability for Efficient PM2.5 Removal from the Pollution Sources

Abstract: Here, we developed high-efficiency (>99.5%) polyimide-nanofiber air filters for the high temperature PM2.5 removal. The polyimide nanofibers exhibited high thermal stability, and the PM2.5 removal efficiency was kept unchanged when temperature ranged from 25-370 °C. These filters had high air flux with very low pressure drop. They could continuously work for >120 h for PM2.5 index >300. A field-test showed that they could effectively remove >99.5% PM particles from car exhaust at high temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
332
2
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 481 publications
(339 citation statements)
references
References 37 publications
3
332
2
2
Order By: Relevance
“…These results are comparable to published studies about vehicle cabin air inlet filters [29], somehow coinciding with the HEPA standards [15,26]. The design of automotive filters is based on their ability to filter particles, which is dependent on the mesh and the structure and composition of the fiber [30]. The analysis of CAFs showed spaces much larger than the fiber diameters, allowing substantial air flow, whereas fibers have a higher specific surface area.…”
Section: Discussionsupporting
confidence: 86%
“…These results are comparable to published studies about vehicle cabin air inlet filters [29], somehow coinciding with the HEPA standards [15,26]. The design of automotive filters is based on their ability to filter particles, which is dependent on the mesh and the structure and composition of the fiber [30]. The analysis of CAFs showed spaces much larger than the fiber diameters, allowing substantial air flow, whereas fibers have a higher specific surface area.…”
Section: Discussionsupporting
confidence: 86%
“…After cleaning, only fewer particles were found, suggesting that the sample CB3 could be reused due to its robustness (Figure E). Furthermore, comparison between CB3 and various porous materials in previous studies is shown in Table . It is demonstrated that as‐prepared CB3 exhibits a relatively high removal efficiency at an ultra‐low pressure drop, and undergoes a much higher testing temperature compared with other materials.…”
Section: Resultsmentioning
confidence: 96%
“…The PM was generated by burning incense and contained particles of sizes from <0.3 µm to >10 µm. 26,27 The PM 2.5 concentration data in the chamber was obtained using an air-quality monitor (BR-SMART 126, Bramc). Temperature data was measured using a digital thermometer (Testo 174T, TESTO).…”
Section: Resultsmentioning
confidence: 99%